2020
DOI: 10.1177/1478077120940975
|View full text |Cite
|
Sign up to set email alerts
|

Integrating expertise and parametric analysis for a data-driven decision-making practice

Abstract: This study explores the integration of expert design intuition and parametric data analysis. While traditional professional design expertise helps to rapidly frame relevant aspects of the design problem and produce viable solutions, it has limitations in addressing multi-criteria design problems with conflicting objectives. On the other hand, parametric analysis, in combination with data analysis methods, helps to construct and analyze large design spaces of potential design solutions and tradeoffs, within a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Although the evidence-based design has endeavored to evaluate healthcare settings' performance from different aspects effectively, applying this process requires a lot of time and labor. The progress of computational design has widely promoted the development of many Computational-Aided Design tools (Bernal et al, 2015(Bernal et al, , 2020. The paper shows how computational design can be expanded to design evidence-based analytical tools to evaluate designs' performance.…”
Section: Discussionmentioning
confidence: 99%
“…Although the evidence-based design has endeavored to evaluate healthcare settings' performance from different aspects effectively, applying this process requires a lot of time and labor. The progress of computational design has widely promoted the development of many Computational-Aided Design tools (Bernal et al, 2015(Bernal et al, , 2020. The paper shows how computational design can be expanded to design evidence-based analytical tools to evaluate designs' performance.…”
Section: Discussionmentioning
confidence: 99%
“…This implementation works as a three-step process: generation, selection, and optimization. The generation process outputs a design space, supported by a custom Design of Experiments for sampling and reducing the size of this design space (Bernal et al, 2020). The selection step is based on designers' preferences within the pool of admissible alternatives.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has been shown that integrated approaches are more efficient than traditional empirical design methods. 26 However, these methods are still under-used by architecture agencies, 7 even if some notable exceptions can be found. 27,28 According to the literature, 1,[29][30][31] there could be many reasons for this underutilization: ideological obstacles, excessive computation time, and lack of training magnified by the multidisciplinary nature of the approach.…”
Section: Literature Reviewmentioning
confidence: 99%